Pembelajaran Bahasa Inggris Berbasis Literasi Digital Pasca Pandemi Covid 19 - Evi Mahsunah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Learning process in the Covid-19 pandemic era obliges teachers to develop methods that are suitable for students' conditions after a long period of online learning. The purpose of this study was to describe digital literacy-based English learning at SMA MA'arif Sidoarjo during the Covid-19 pandemic. This data was taken using observation of the learning process and interviews with teachers and students about the digital literacy-based English learning process. The results showed that the learning had been carried out face-to-face and the implementation of digital literacy-based English learning at SMA Ma'arif Sidoarjo was going well based on the 3 levels development of digital literacy. The first level, digital competence shows that all teachers and students have good skills in using internet-based digital devices in the learning process and polite student behavior in social media. Second, digital usage that used by teachers in delivering learning, finding other references such as pictures, videos, or texts related to the material. The last level, namely digital transformation, emerges from the creativity of teachers in developing innovative teaching materials and learning media. Then, students' creativity in doing assignments have been uploaded on Youtube and social media.